2003
DOI: 10.1177/0898264303256198
|View full text |Cite
|
Sign up to set email alerts
|

Educational Attainment, Positive Psychological Mediators, and Resources for Health and Vitality in Older Adults

Abstract: Higher education level appears to increase the likelihood of being serene and happy, and healthy and vital, in later years; positive psychological states appeared to have both a promotion function (for vitality) and protective function (against health symptoms); self-esteem showed promise as a possible mediator of the effects of psychological states on health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 55 publications
4
43
0
1
Order By: Relevance
“…Several cross-sectional studies have shown associations between depression or depressive symptoms and fatigue (17,135) and development of fatigue (15,136,137). However, when adjusting the associations between fatigue and diverse outcomes by depressive symptoms, the results did not seriously change (33,58,62,64).…”
Section: Depressionmentioning
confidence: 80%
“…Several cross-sectional studies have shown associations between depression or depressive symptoms and fatigue (17,135) and development of fatigue (15,136,137). However, when adjusting the associations between fatigue and diverse outcomes by depressive symptoms, the results did not seriously change (33,58,62,64).…”
Section: Depressionmentioning
confidence: 80%
“…Educational attainment is associated with happiness in older people (Kubzansky et al, 1998;Murrell et al, 2003). Those born before 1956 in the UK were not legally obliged to stay at school until age 16 (Sheldon, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In general, positive states of well-being correlate with better physical health (e.g., Hilleras, Jorm, Herlitz, & Winblad, 1998;Murrell, Salsman, & Meeks, 2003;Ostir, Markides, Black, & Goodwin, 2000). Correlations between objective physical health (i.e., health as assessed by medical personnel) and well-being are low in broad samples of respondents, in part because people appear to adapt over time to many illnesses and because most people are relatively healthy.…”
Section: Physical Health and Well-beingmentioning
confidence: 99%